PROFESSIONAL SPECIFICITY OF CONCEPTUAL THINKING - S. A. Gilmanov (Образование и наука)
Introduction. Most studies of psychologists and teachers in the phenomenon of conceptual thinking and ways of its formation are considered to be rather controversial and questionable. However, the research results were limited to the phenomenon of conceptual thinking and are therefore not representative for its implementation during the process of vocational training at the higher school. There is still considerable uncertainty with regard to the approaches to the problem of conceptual thinking in the humanities, including pedagogics and psychology. Furthermore, previous studies have not dealt with the objectives of conceptual thinking formation.The aims of the article are: to justify the use of the term “professional conceptualization of thinking” (PCT) in theory and practice; to describe the prospects of the development of PCT in the training process.Methodology and research methods. The methodological base of the research involves the Russian psychological and pedagogical science approaches to the consideration of conceptual thinking as a higher mental function, a systematized and summarized form of cognitive reflection of notions and relations of reality. The experimental work was carried out using the method of observation, interviews, and tests. Quantitative and qualitative analysis of the data was conducted. The process of formation of PCT is described through the theory of stage-by-stage systematic development of mental acts.Results and scientific novelty. The concept “professional conceptualization of thinking” (PCT), a new one for psychological-pedagogical science, is suggested. The PCT levels are identified: ordinary, formal, substantial, system, and holistic. The objectives proposed for the development of the PCT levels in the process of professional education consist in the organization of consecutive transition from conscious mastering of a terminological framework to its use in the performance of educational tasks; from understanding the logic of the solution of professional tasks to development of logic of professional activity; from the student's position as a participant of interaction with a teacher to the position of a member of professional activity. The author refers to the need of: continuous stimulation for students’ work during the process of understanding the relationship of concepts with intrinsic properties of objects; role definition of conceptual reflection of reality presented in the chain “aim of task solution – objects – their properties – a task – actions”.Practical significance. The findings of the study, approaches to development of PCT and the author’s recommendations can be used in teaching both psychological-pedagogical disciplines and other disciplines in higher education institutions.